235 Antigen presentation pathways prime melanoma patients for more durable response to anti–PD-1 checkpoint blockade therapy. (10th December 2020) - Garg, Saurabh; Welsh, Eric; Fang, Bin; Hernandez, Yuliana; Rose, Trevor; Gray, Jhanelle; Koomen, John; Berglund, Anders; Mule, James; Markowitz, Joseph
Abstract : Background: Favorable outcomes utilizing anti–PD-1 based immune therapies for unresectable melanoma patients are hypothesized to be dependent on antigen processing and presentation mechanisms. The present study utilizes multiomics to examine the contribution of antigen presentation pathways in metastatic melanoma tumors either responsive or resistant to anti-PD-1 therapy. Methods: To unveil the mechanisms that predispose unresectable, stage III/IV melanoma patients to respond to anti–PD-1-based therapies, we conducted expression proteomics as well as employed the mRNA immune oncology panel (HTG Molecular Diagnostics, Inc., Tucson, AZ). Formalin-fixed, paraffin-embedded tissues collected from 27 patients prior to anti-PD-1 therapy (previously consented and enrolled in the Moffitt Cancer Center Total Cancer Care (TCC) protocol) were utilized in this study. For the proteomics analysis, we examined 19 FFPE samples, whereas the targeted mRNA analysis utilized 25 FFPE samples with 17 samples analyzed using both omics approaches. Robust mass spectrometry analysis used a pooled sample to optimize the number of detected peptides. The melanoma patients were selected from the database based on whether they had progression free survival (PFS) greater than 1 year (n=15) or PFS less than 6 months (n=12). Results: We identified more than 250 transcript/protein candidates that demonstrated differential expression between poor and good responders following anti-PD-1 therapy. Utilizing MetaCore software and subsequent downstream analyses of expression profiles for a knowledge-based curation of pathways and protein networks, we illustrated both the enrichment of Gene Ontology (GO) terms and specific antigen processing/presentation proteins. Of the top 10 GO processes, 7 were related to antigen processing/presentation and Major Histocompatibility Complex (MHC) presentation. Antigen processing/presentation and cytokine production/signaling via IFN-γ–mediated signaling through NF-κB and the JAK/STAT pathway interaction with iNOS were mechanistic candidates of response to anti-PD-1 therapy. Conclusions: These comparative analyses illustrated the importance of antigen processing/presentation pathways mediated by both MHC class I and II in activating the immune system to initiate and maintain the immune-based response to anti–PD-1 therapy in metastatic melanoma patients. The current study also demonstrated the value of proteogenomics in defining mechanisms of response and resistance to anti-PD-1 therapy. Trial Registration: N.A. Ethics Approval: The procurement of FFPE samples was approved under IRB-approved protocol (MCC 18583, Advarra) from patients who had received a biopsy within 1 year prior to the start of anti–PD-1 therapy. Biopsy samples were obtained from the institutional biobank (Total Cancer Cancer). The radiology reads (performed by T.R.) from this research were funded by a parent research project to Moffitt Cancer Center by Navigate BioPharma to J.G. and J.M. Consent: N.A.